Social and biological early life influences on the prevalence of open bite in Brazilian 6-year-olds - KAREN GLAZER PERES, MARIA DO ROSÃƒÆ’Ã‚ÂRIO DIAS DE OLIVEIRA LATORRE, AUBREY SHEIHAM, MARCO AURÃƒÆ’Ã (IAPD and Blackwell, 2007)
Little is known about the effects of social and biological risk factors for open bite on the primary dentition. The aim of this study wasto assess the early-life risk factors affecting anterior open bite.